Poezja Niny Berberowej. Wstępne rozpoznania teoretyczne - Brzykcy, Jolanta (Studia Rossica Posnaniensia, 2026)
The subject of this article is the place of poetry in the literary output of Nina Berberova (1901–1993), a representative of the first wave of Russian emigration, author of short stories and novels about the life of the Russian diaspora, biographical prose (including works about A. Blok, A. Borodin and P. Tchaikovsky) and the famous autobiography The italics are mine (1969). Her poems have been pushed into the background of readers’ interests and academic reflection by her prose; they are less well known and have not yet been the subject of separate literary studies in Poland. Recognising this gap in research on Berberova’s work, I reflect on the reasons for the marginalisation of her poetry. I also attempt to determine its place in Berberova’s oeuvre based on her creative biography and the way it is highlighted in her autobiography. Both the facts from Berberova’s life and their presentation in her autobiography prove that poetry was an important part of her literary legacy and also crucial factor in shaping her identity. This article serves as an introduction to further research on Berberowa’s poetry, including an analysis of her poems.